Potensi Cemaran Kandungan Minyak Lemak (Oil and Grease) Limbah Cair PT. Perikanan Sejahtera dan PT. Tuban Kretek Maju Di Kabupaten Tuban, Jawa Timur: Potential Contamination of Fatty Oil Content (Oil and Grease) Liquid Waste PT. Perikanan Sejahtera and PT. Tuban Kretek Maju In Tuban Regency, East Java - Akhmad Farid; Eka Nadia Aprillina (LPPM Universitas Mataram, 2023)
Wastewater from the result of industrial activities such as PT. Perikanan Sejahtera dan PT. Tuban Kretek Maju, with the characteristics of the numbr pf supporting and main parameters that still meet the waste water quality standards. Waste water is processed and treated fisrt before being discharged directly into receiving water bodies so that ut does not have an adverse impact on the aquatic environment. Sampling test samples of wastewater were taken directly from the IPAL outlets of each PT. This study aims to determine the potential for water pollution drom oil and grease content at two PT. different. The research method is observation and active participation method. Determination of potential quality of domestic wastewater in accordance with the Regulation of the Minister of Enviromental of the Republic of Indonesia No. 5 of 2014. The pH value is determined based on (SNI 6989.11:2019), the temperature value is determined based on (06-6989.23:2005) and the fatty oil value is determined by the gravimetry method according to (SNI 6989.10:2011). The results the research on the pH value of the samples of PT. Perikanan Sejahtera dan PT. Tuban Kretek Maju is 7,80 and 7,67, the temperature value is 31,0 and 32,6. Meanwhile, the values for oil and fat content were 1.850 mg/L and 1.800 mg/LOil and fat figures are not too significant, showing too much difference in the test samples. Waste water from each PT. does not have a large potential to cause pollution of the water environment in the parameters of oil and grease.